Facing World Religion Paradigm: Challenges Of Dayak Kaharingan During New Order Era Into Reforms - Rosyadi, Muhammad Sandi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
Belief, as part of human life, is part of the fundamental rights. However, the increasing number and variety of existing beliefs impact the emergence of standardized beliefs that deserve to be categorized as religion. This paper discusses how one of the original beliefs of the people of Kalimantan, namely kaharingan, cannot be considered a religion because various religious standards hamper it. This paper finds that standardization which begins with the notion of religion, according to EB Taylor, has an impact on a belief that must meet several conditions, such as belief in God, holy scriptures, carriers of religion or prophets, and others. The standardization impacts Kaharingan as a belief that can only be said as a